Diversity, Abundance, and Traditional Uses of Asteraceae Species in Mount Bisma, Dieng Plateau, Kejajar, Wonosobo, Central Java - Bima Kurniawan; Purnomo Purnomo; Rina Sri Kasiamdari (Journal of Tropical Biodiversity and Biotechnology, 2022)
Asteraceae is the largest and most diverse family of flowering plants which contains more than 20,000 species distributed in nearly all types of habitats all over the world. In mountainous regions such as Mount Bisma, it is estimated to have plenty and diverse member of the Asteraceae family, and used in the local community for various uses. This research aimed to understand the diversity, abundance, and uses of Asteraceae members that are found wild in Mount Bisma. Taxonomy and ecological data were gathered using an exploration method and purposive sampling method, from the point, a plot measured 3x3 m2 was created to estimate the vegetation parameters in the mountain top and mountain valley area. Ethnobotanical data were gathered in Sikunang Village, a nearby village of Mount Bisma using a semi-structured interview and open-ended questions. Data were analysed descriptively and quantitatively using several indices such as Importance Value Index (IVI), Index of Cultural Significance (ICS), and index of Use Value (UV). The result showed that there were 18 species from two subfamilies that grew wild in both mountain top and valley of Mount Bisma. The highest importance value belonged to Ageratina riparia, which was scored in the mountain top and valley 71.00 and 91.53, respectively. Uses of Asteraceae in Sikunang were varies, ranging from being a side dish, medicine, firewood, souvenir, and other uses. Galinsoga parviflora and Galinsoga quadriradiata showed the highest ICS value of 41, whereas Austroeupatorium inulifolium scored the highest in UV of 1.8. The study presented high number of Asteraceae diversity and use. Thus, implies that Mount Bisma has vast unexplored biodiversity and locals around Mount Bisma have rich traditional knowledge.